Makna Konseptual dan Makna Asosiatif Pada Serial Musikal Nurbaya dan Relevansinya Pada Keterampilan Mementaskan Drama - Nanda Sherliana; Muhamad Haryanto (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to describe the conceptual meaning and associative meaning of the Nurbaya Musical Series on the Indonesia Kaya youtube channel, The results of the research will be relevant to drama learning at class XI high school level, the research method used in this research is qualitative descriptive research using a literature study approach. The data used in this research consists of words and sentence fragments that contain conceptual meaning and associative meaning. The data source that is the focus of this research is the Nurbaya Musical Series on the Indonesia Kaya youtube channel. The data collection technique in this research uses library study techniques, listening, phrase, and taking notes. Data analysis techniques are descriptive qualitative. The results of research analyzing conceptual meaning and associative meaning in the Nurbaya Musical Series which consists of six episodes, found conceptual meaning and associative meaning. The type of associative meaning in this research are collocative meaning and connotative meaning. The results of this research can be relevant in drama learning at class XI high school level, in learning objective 3.18 Identify the story line, act by act, and conflict in the drama you read or watch. As well as learning objective 4.18 Demonstrate one of the characters in a drama that is read or watched orally